A Multi-Mode Bioactive Agent Isolated From Ficus microcarpa L. Fill. With Therapeutic Potential for Type 2 Diabetes Mellitus - Akhtar, Nosheen; Jafri, Laila; Green, Brian D; Kalsoom, Saima; Mirza, Bushra (Frontiers in Pharmacology, 2018)
Type 2 diabetes is a metabolic disorder, characterized by hyperglycemia and glucose intolerance. Natural products and its derived active compounds may be achievable alternatives for the treatment of type 2 diabetes. In present study we investigated the antidiabetic potential of Ficus microcarpa and isolated bioactive compounds i.e., Plectranthoic acid (PA) and 3,4,5,7-Flavantetrol (FL). Anti-hyperglycemic potential was evaluated via α-glucosidase, α-amylase and dipeptidyl peptidase 4 (DPP-4) assays. 5’AMP-activated kinase (AMPK) activation potential was assessed by using primary hepatocytes. Distribution of PA in different parts of Ficus microcarpa was evaluated by using rapid high-performance liquid chromatography (HPLC). Ethyl acetate fraction (FME) exhibited significant inhibition of α-glucosidase, α-amylase, and DPP-4, therefore, was selected for isolation of bioactive compounds. Among isolated compounds PA was more potent and possessed pleotropic inhibitory activity with IC50 values of 39.5, 55.5, and 51.4 μM against α-glucosidase, α-amylase, and DPP-4, respectively. Our results showed that PA is also a potent activator of AMPK which is a central hub of metabolic regulation. Molecular docking studies confirmed the activity of PA against α-glucosidase, α-amylase, and DPP-4. Rapid HPLC method revealed that maximum concentration of PA is present in the stem (2.25 μg/mg dry weight) of Ficus microcarpa. Both in vitro and in silico studies proposed that Ficus microcarpa and its isolated compound PA could be an important natural source for alleviating the symptoms of type 2 diabetes mellitus and we suggest that PA should be explored further for its ultimate use for the treatment of type 2 diabetes.